Adaptação transcultural e validação de conteúdo da Escala Attitudes about Poverty and Poor People - Izabela Thaís de Magalhães Neto (2021)
Introduction: Poverty is a global problem and one of the main causes of health problems. In order to overcome poverty, it is important that, in addition to recognizing it, acting on it is part of the work of professionals from different categories and areas of knowledge. Nursing education can respond to this challenge by incorporating the social determinants of health and its relationship with poverty in its curricular components. In Brazil, no studies dealing with the curricular approach to poverty in undergraduate nursing were identified. It is understood that this problem is due to the lack of specific assessment of the approach to poverty in nursing education. Thus, this encourages the need to define specific instruments that can represent the understanding of this phenomenon in the national reality and directs us to a methodological study of cross-cultural adaptation of a scale capable of measuring the teaching of poverty in nursing education. Objective: To carry out the cross-cultural adaptation of a scale of attitudes about poverty for nursing students. Method: This is a methodological study of cross-cultural adaptation of a scale of attitudes about poverty for nursing students. The following phases were followed: selection of a scale, through an integrative literature review; Translation; synthesis; back translation; meeting with translators; meeting with experts; content validation; pretest and cognitive interviews. The scale application sample consisted of 10 nursing students from a public higher education institution. Data were tabulated in Microsoft Excel and presented using the Statistical Package for Social Sciences software version 19.0. The interviews were transcribed in full with the help of the InqScribe software and organized according to the items that students had difficulty understanding in the MaxQDA Analytics Pro 2020 20.4.0 software. The research was only initiated after authorization for translation of the scale and approval by the Research Ethics Committee. Results: The scale selected was Attitudes about Poverty and Poor People. The items of the scale translated into Brazilian Portuguese were evaluated for semantic, idiomatic, experiential and conceptual equivalence. Items 10 and 30 presented a Content Validity Index lower than 0.8, a reference value adopted in the research. These items underwent adjustments and went through a second round, showing 100% agreement among the judges. The 37 items had an internal consistency measured by Cronbach's Alpha of 0.839 indicating a strong association of the entire scale, and reliability measured by Split-half (odd vs even) of 0.859, indicating a high correlation between the two halves, odd and pair. The results of the interviews revealed problems related to assimilation, interpretation, complex sentences and semantics. Interpretation problems were the main ones in the interviews and were present in nine items. Conclusion: Although the scale translated into Portuguese presented satisfactory content validity, reliability and internal consistency, in the cognitive interview, an important strategy, it was possible to detect measurement problems by nursing students. The scale translated into Portuguese and adapted to the Brazilian reality can contribute to the recognition of poverty as a multidimensional structural phenomenon of deprivation that goes far beyond income. In Nursing Education, the scale can identify whether education has been promoting positive attitudes that are attentive to the health needs of the population living in poverty.